A Study on Human Factor That Lead To Tower Crane Accident At Construction Site In Malaysia - Ramalan, Affiq Haikal; Hasmori, Muhammad Fikri (Recent Trends in Civil Engineering and Built Environment, 2021)
Tower crane act as the lifeline in the construction industry, but accidents that related to tower crane operation still often occur. Loss of life, death, and harm to the property are the implications that will arise if the crane handling processes and standards are not properly performed. There are several factors that affect the safety of tower crane operation in construction that can be put into four main factors that are project condition, environment, human factor and safety management. From those factors, the human factor is the most common reason for the accident that related to tower crane operation to occur. Human error such as lack of communication, inexperienced worker, disobeying the safety procedure that provided and lack of supervision has been the contributor to this accident happened. This research, therefore, addressing the issue about the most common causes of tower crane accidents that happen on the construction site. This research further examine the human factor that causes tower crane accident and propose recommendation in minimizing human-related error in a tower crane accident. All information and data were obtained by using Pilot study and questionnaire surveys in Google form that were distributed to the professionals such as tower crane operator, site engineer, site safety supervisor, safety officer and further studies of crane accident cases in Malaysia. The responses achieved shows that majority of the respondents strongly agree that tower crane shall be operated by a competent person who holds a valid competency certificate issued by DOSH Malaysia and the recommendation to reduce tower crane accident is each tower crane operator shall carry out daily the pre-operation safety inspection checklist to avoid further problem during tower crane handling process.